Widyaiswara's Role in Apparatus Development in the Pandemic and New Normal Era - Ita Hartati; Azwar Iskandar (Budapest International Research and Critics University, 2021)
This research aims to provide an overview of the challenges and role of Widyaiswara in the Ministry of Finance in improving ASN competence through adaptation and innovation in the pandemic and new normal era. Using a qualitative descriptive approach, this study found that widyaiswara is required to be able to think creatively and innovatively. The challenge is whether widyaiswara is able to make interesting multimedia teaching materials. Widyaiswara was challenged and required to continue to improve and change. Widyaiswara should be able to utilize technology to open the horizon of thinking and view technology as an opportunity to improve ASN competence in the future. To answer the challenges and demands of change in this pandemic and new normal era, widyaiswara can act as facilitator, motivator, inspiration, innovator, dynamicator and role model through innovation and adaptation in the pandemic era and new normal through its roles in aspects of bureaucracy efficiency, digital literacy, agile organization mindset, public service responsiveness, and integrated and flexible working space.